2009
DOI: 10.1002/lt.21700
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment for biliary stricture after adult living donor liver transplantation

Abstract: Endoscopic intervention is considered to be the primary treatment for biliary stricture after adult living donor liver transplantation (LDLT) with duct-to-duct biliary reconstruction. The aim of this study was to investigate the risk factors of biliary stricture and the clinical outcomes and predictors of failure after endoscopic retrograde cholangiography with balloon dilation (ERC-D). We enrolled 239 adult patients who underwent LDLT between 2000 and 2006. Sixty-eight patients (28.4%) developed biliary stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 43 publications
6
110
1
3
Order By: Relevance
“…Of the four bile leaks in our study, all except one underwent ERCP and stenting. Surgery is reserved for endoscopic failure or when bile leak causes generalized peritonitis [14]. None of our patients needed urgent laparotomy.…”
Section: Management Of Biliary Complicationsmentioning
confidence: 88%
“…Of the four bile leaks in our study, all except one underwent ERCP and stenting. Surgery is reserved for endoscopic failure or when bile leak causes generalized peritonitis [14]. None of our patients needed urgent laparotomy.…”
Section: Management Of Biliary Complicationsmentioning
confidence: 88%
“…However, results of endoscopic maneuvers are disappointing for biliary strictures after LDLT, and the success rate is 60∼75% for anastomotic strictures (1,4,6,7,11-15). The causes for the low success rates of endoscopic intervention therapy are the presence of multiple ductal anastomoses, smaller size, peripheral location, and a pouched shape of biliary anastomosis (3,6,14,16). In right hemi-liver-LDLT patients with duct-to-duct biliary reconstruction, most anastomotic biliary strictures develop in a fork-shaped or trident-shaped fashion even if the biliary system had been reconstructed in a single duct-to-duct fashion (15).…”
Section: Discussionmentioning
confidence: 99%
“…The success rates of endoscopic treatment for anastomotic strictures in LDLT are significantly lower than in DDLT at 60∼75% (3)(4)(5)(6). In failed cases, a percutaneous approach can be attempted.…”
Section: Difficult(4)mentioning
confidence: 99%
“…Some studies have suggested that biliary stricture occurs more frequently in post-LDLT patients than in deceased liver transplantation because of the small diameter of the anastomotic portion of the bile duct, anatomical diversity of the bile ducts, or the complicated nature of the surgical procedure [9,10,18] . There are two strategies for treating anastomotic strictures: via the endoscopic retrograde approach [19] or the percutaneous transhepatic approach [20] .…”
Section: Ir For Anastomotic Biliary Stenosismentioning
confidence: 99%
“…Moreover, biliary complications remain common after LDLT, and some studies suggested that biliary stricture at the anastomotic site occurs more frequently in post-LDLT patients than in deceased liver transplantation. This is because of the small diameter of the anastomotic portion of the bile duct, anatomical diversity of the bile ducts or the complicated nature of the surgical procedure [9,10] .…”
Section: Introductionmentioning
confidence: 99%